Input and output of energy in processing gizzard pickle - A. K., Sachder; K. P., Mishra; Gopal, Ram; S. S., Verma (Universiti Putra Malaysia Press, 1995)
Data were collected from seven replicates to quantify the input of commercial energy in manual processing of oil based (OB) as well as vinegar-based (VB) chicken gizzard pickles and output of caloric values from the products was calculated. Higher amounts of electrical (0.691 kWh) and total energy (9.792 kWh) with lesser inputs of human energy were required in preparation of VB pickle compared with 0.3 (0.597 kWh) and 8.731 M]lkg of raw gizzard products. However, more caloric outputs were obtained from OB product (282 Cal/l00g) compared with VB (261 Cal/l00g) pickle. Despite significant superiority of oil-based gizzard pickle for colour, juiciness and tenderness, the overall acceptability of pickles was insignificantly different. Proximate analysis revealed non significant variations in pH, moisture content and crude protein of the two pickles. Based on the input output energy relations, it is concluded that processing of experimental VB gizzard pickle is economically cost effective (67 Call rupee) over the oil-based (56 Cal/rupee) chicken gizzard pickle.